# 2ln(x)=ln(25)

## Simple and best practice solution for 2ln(x)=ln(25) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 2ln(x)=ln(25) equation:

Simplifying
2ln(x) = ln(25)
Multiply ln * x
2lnx = ln(25)
Reorder the terms for easier multiplication:
2lnx = 25ln
Solving
2lnx = 25ln
Solving for variable 'l'.
Move all terms containing l to the left, all other terms to the right.
Add '-25ln' to each side of the equation.
-25ln + 2lnx = 25ln + -25ln
Combine like terms: 25ln + -25ln = 0
-25ln + 2lnx = 0
Factor out the Greatest Common Factor (GCF), 'ln'.
ln(-25 + 2x) = 0
Subproblem 1Set the factor 'ln' equal to zero and attempt to solve:
Simplifying
ln = 0
Solving
ln = 0
Move all terms containing l to the left, all other terms to the right.
Simplifying
ln = 0
The solution to this equation could not be determined.
This subproblem is being ignored because a solution could not be determined.
Subproblem 2Set the factor '(-25 + 2x)' equal to zero and attempt to solve:
Simplifying
-25 + 2x = 0
Solving
-25 + 2x = 0
Move all terms containing l to the left, all other terms to the right.
Add '25' to each side of the equation.
-25 + 25 + 2x = 0 + 25
Combine like terms: -25 + 25 = 0
0 + 2x = 0 + 25
2x = 0 + 25
Combine like terms: 0 + 25 = 25
2x = 25
Add '-2x' to each side of the equation.
2x + -2x = 25 + -2x
Combine like terms: 2x + -2x = 0
0 = 25 + -2x
Simplifying
0 = 25 + -2x
The solution to this equation could not be determined.
This subproblem is being ignored because a solution could not be determined.
The solution to this equation could not be determined.`